Arduino meets MATLAB: Interfacing, Programs and Simulink - Anita Gehlot, Rajesh Singh, Bhupendra Singh (Bentham Science Publishers, 2018)
This book provides a single platform for beginners in systems engineering to start Arduino interface projects with MATLAB®. It covers the basics of the programming with Arduino and Arduino interfacing with MATLAB® with and without the use or I/O packages.